Meningkatkan Hasil Belajar Ikatan Kimia Dengan Menerapkan Strategi Pembelajaran Peta Konsep Pada Siswa Kelas X di SMA Negeri I Telaga - Ismail, Muratni; Laliyo, Lukman A.R.; Alio, La (Jurnal Entropi, 2013)
This research is a class action research, which has purpose to increase student's learning achievement in chemical-bond subject by using concept-mapping strategy. The sample of this research is 31 students of 10th2 Grade at SMA Negeri 1 Telaga that consist of 6 girls and 25 boys.The increase of student's learning achievement by using concept-mapping strategy can be seen from the cycle 1 as high as 80.08% to cycle 2 as high as 85.79%.Based on the result above, the treatment hypothesis "concept-mapping strategy can be used to increase student's learning achievement in chemical-bond subject" is approved.